Pengaruh Variasi Konsentrasi Inhibitor Ekstrak Daun Kakao (Theobroma Cacao) Terhadap Laju Korosi Baja ST 37 Dalam Larutan HCl 3% - Syafriadi Syafriadi; Risca Adriana; Agus Riyanto (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The effectiveness of cacao leaf extract (Theobroma Cacao.) used as an inhibitor on St 37 steel sample. Which cures in HCl 3 % Corrosive Medium for 144 hours, the inhibitor concentration variation added 0 %, 3%, 6 %, 9 %, and 12 %, respectively. The sample rate is measured by using the loose-weight method. The results show that the lowest sample is 1.397 mm/y of 12%, and the highest is 3.694 mm/y of 0 %. Inhibitor efficiency to the sample St 37 Stainless steel portrays adequate progress to 62.66% with 12% concentration. X-Ray Diffraction Results acquired BCC with Fe-a phase along with SEM that forms an agglomeration, cracked, and holes which result in its corrosion. In addition, EDS contains FeO Element, which indicates that stainless is still affected by corrosion and the reduced FeO content in the sample was less. Thus three samples characterized and measured show that avocado leaves effectively as an inhibitor to the sample St 37 in HCl 3% corrosive medium.